A systemetic Review on Security, Strength and Core of 5G - Kulkarni, Anju V.; Sasi, Smitha; Menon, Radhika; Venkatesan, Mithra (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The creation of next-generation wireless networks is projected to provide rapid connectivity and low-latency connections in daily life. As a result, network security is essential. The increase in gadgets and the range of facilities that 5G provides have made the environment for network security more difficult. This is exactly it’s so important to go to work on workable security solutions right away. The findings of our analysis have demonstrated the several ways that modern wireless network growth will take. Artificial intelligence and software-defined mobile networks are two of them.